2021
DOI: 10.1111/jnc.15322
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of the Rho GTPase Rnd3 triggers developmental defects in internal capsule and the globus pallidus formation

Abstract: The forebrain includes the cerebral cortex, the thalamus, and the striatum and globus pallidus (GP) in the subpallium. The formation of these structures and their interconnections by specific axonal tracts take place in a precise and orchestrated time and spatial-dependent manner during development. However, the knowledge of the molecular and cellular mechanisms that are involved is rather limited. Moreover, while many extracellular cues and specific receptors have been shown to play a role in different aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(233 reference statements)
0
4
0
Order By: Relevance
“…Our previous results demonstrated that Rnd3 deficient mice show alterations both in the structure and the function of the CNS (Mocholi et al, 2011;Ballester-Lurbe et al, 2015;Kaur et al, 2020;Madrigal et al, 2021;Marfull-Oromi et al, 2021). To determine if there were defects also at the subcellular level, we analyzed brain sections at the subventricular zone (SVZ) by electron microscopy (Figure 1A), where we had previously described several alterations (Ballester-Lurbe et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous results demonstrated that Rnd3 deficient mice show alterations both in the structure and the function of the CNS (Mocholi et al, 2011;Ballester-Lurbe et al, 2015;Kaur et al, 2020;Madrigal et al, 2021;Marfull-Oromi et al, 2021). To determine if there were defects also at the subcellular level, we analyzed brain sections at the subventricular zone (SVZ) by electron microscopy (Figure 1A), where we had previously described several alterations (Ballester-Lurbe et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Rnd3 has an essential role in cell migration along the rostral migratory stream (RMS) and is crucial for proper olfactory bulb cell development ( Ballester-Lurbe et al, 2015 ). Finally, we have recently described that Rnd3 is necessary for the formation of dendritic spines and the corticospinal axon pathfinding as well as in the globus pallidus formation ( Kaur et al, 2020 ; Marfull-Oromi et al, 2021 ). These and other evidence point out the important role of Rnd3 in neurodevelopment, although the molecular mechanisms involved are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit anti-TH was purchased from BioLegend, catalog no. 818002 ( 84 , 85 ). Mouse anti-FLAG antibody was purchased from Sigma Aldrich, catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we have recently described that Rnd3 expression in corticospinal neurons is necessary for the formation of dendritic spines and extended axons and that Rnd3 maintains the radial glial scaffold at the striatopallidal junction that facilitates corticospinal axon pathfinding (Kaur et al 2020). In addition, the absence of Rnd3 expression produces several defects in striatal and thalamocortical axonal projections as well as in the globus pallidus formation at early developmental stages (Marfull-Oromí et al 2021).…”
Section: Introductionmentioning
confidence: 99%